CXCR4-using HIV variants in a cohort of Black men who have sex with men: HIV Prevention Trials Network 061. Issue 4 (3rd July 2016) - Chen, Iris; Huang, Wei; Connor, Matthew B.; Frantzell, Arne; Cummings, Vanessa; Beauchamp, Geetha G.; Griffith, Sam; Fields, Sheldon D.; Scott, Hyman M.; Shoptaw, Steven; del Rio, Carlos; Magnus, Manya; et al.
Abstract : Objective: To evaluate factors associated with HIV tropism among Black men who have sex with men (MSM) in the United States enrolled in a clinical study (HIV Prevention Trials Network 061). Methods: HIV tropism was analyzed using a phenotypic assay (Trofile assay, Monogram Biosciences). Samples were analyzed from 43 men who were HIV infected at enrollment and reported either exclusive insertive intercourse or exclusive receptive intercourse; samples were also analyzed from 20 men who were HIV uninfected at enrollment and seroconverted during the study. Clonal analysis of individual viral variants was performed for seroconverters who had dual/mixed (DM) viruses. Results: DM viruses were detected in samples from 11 (26%) of the 43 HIV-infected men analyzed at the enrollment visit; HIV tropism did not differ between those reporting exclusive insertive vs receptive intercourse. DM viruses were also detected in five (25%) of the 20 seroconverters. DM viruses were associated with lower CD4 cell counts. Seroconverters with DM viruses had dual-tropic viruses only or mixed populations of CCR5- and dual-tropic viruses. Conclusions: DM viruses were frequently detected among Black MSM in this study, including seroconverters. Further studies are needed to understand factors driving transmission and selection of CXCR4- and dual-tropic viruses among Black MSM.